Empowerment of PAI Supervisors Through Supervisory Working Groups - Baehaqi, Anan; Wasliman, Iim; Iriantara, Yosal; Tedjawiani, Ida (International Journal of Educational Research & Social Sciences, 2022)
Empowerment of PAI Supervisors through the Supervisory Working Group (Research on PAI Pokjawas West Java Province). The research problem starts from the strategic position of Pokjawas as a supervisory organization for PAI supervisors but, on the one hand, shows the low competence of PAI supervisors and the lack of competency development by the authorities. That became the foundation of Kindervatter's theory of empowerment. This research aims to explore the implementation of PAI supervisor empowerment through Pokjawas in West Java Province. Specifically, it is to find out the efforts of Pokjawas The results showed that the appointment of PAI supervisors through Pokjawas in the form of (1) developing the potential (enabling) of PAI supervisors indicated by the existence of a supervisory competency development program, developing supervisory resources, building and encouraging the independence of the new supervisors for the most part; (2) building the power (empowering) of PAI supervisors is made by reinforcing to improve the competence of PAI supervisors that are already running, but not yet PAI supervisors are involved in this (3) protecting by fighting for the rights of members so that PAI supervisors feel calm, comfortable and prosperous in carrying out their duties (4) innovating for PAI supervisors by developing supervisory information systems and technology, developing supervisory supervision models, utilizing organizational information media to improve supervisory competence.